PORCELAIN. (19th June 2018) - Moore, Kate
Abstract: Time through history can be marked by the passing of generations. Archeological sites reveal the intimate secrets of our ancient ancestors through thousands of pieces of broken pottery recovered from the ground. Piecing together these shards can be likened to reconstructing a jigsaw puzzle, one of long forgotten civilisations, places, memories and stories.